Experimental analysis of nano and engineering materials and structures proceedings of the 13th International Conference on Experimental Mechanics, Alexandroupolis, Greece, July 1-6, 2007 - Gdoutos, E. E. (Springer, 2007)
This volume contains two-page abstracts of the 482 papers presented at the latest conference on the subject, in Alexandroupolis, Greece. The accompanying CD contains the full length papers. The abstracts of the fifteen plenary lectures are included at the beginning of the book. The remaining 467 abstracts are arranged in 23 tracks and 28 special symposia/sessions with 225 and 242 abstracts, respectively. The papers of the tracks have been contributed from open call, while the papers of the symposia/sessions have been solicited by the respective organizers.--Provided by publisher.